Pengaruh intensifikasi pajak dan ektensifikasi pajak terhadap penerimaan pajak di era pandemi covid-19 (studi empiris pada Kantor Pelayanan Pajak Pratama Mojokerto) - Endah Kartika Gita; Agus Haryono; Dyah Ani Pangastuti (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
This research aims to analyze the impact of tax intensification and tax extensification on tax revenue in the covid-19 pandemic era at the Mojokerto Primary Tax Service Office. The independent variables in this research consist of tax intensification and tax extensification. While the dependent variable in this research is tax revenue. This research uses Multiple Linear Regression Analysis. The type of data in this research is secondary data, time series data as much as 60 months for 5 years, from January 2016 to December 2020. The results of this research show that partial tax intensification has a significant effect on tax revenue in the era of the covid-19 pandemic, while partial tax extensification has no significant effect on tax revenue in the covid-19 pandemic era at the Mojokerto Primary Tax Service Office. However, tax intensification and tax extensification simultaneously have a significant effect on tax revenue during the covid-19 pandemic at the Mojokerto Primary Tax Service Office